Pretreatment with dimethyl fumarate prevents chronic pain and its comorbidities via Nrf2 pathway in a rat model of neuropathic pain - Le, Cong Tuan Anh; Fiuza-Fernandes, Juliana; Silva, Joana Margarida; Sampaio, Mariana Teixeira; Texeira-Castro, Andreia; Duarte-Silva, Sara; Leite-Almeida, Hugo (Brain, behavior and immunity, 2025)
Chronic pain susceptibility varies across individuals, and the immune system, among other factors, appears to be involved in this variability. This study aims to examine whether modulating the immune system around the inciting events provides protection against the development of chronic pain and related comorbidities. Dimethyl fumarate (DMF) - an immunomodulator - or vehicle (VEH) was administered 7 days before spared nerve injury (SNI) in Wistar Han male rats. After the surgery, half of the animals from each group shifted treatments for an additional 7 days, resulting in 4 groups: continuous treatment (DMF-DMF), pretreatment (DMF-VEH), early treatment (VEH-DMF), and control (VEH-VEH). As a result, DMF-DMF, DMF-VEH, and VEH-DMF reduced allodynia and attenuated anhedonia measured at 4 weeks post-SNI, compared to VEH-VEH. VEH-DMF increased serum protein levels of anti-inflammatory markers, including IL-10 and G-CSF, and those pleiotropic, such as IL-6, IFN-g, and IL-17A. The leptin reduction seems to be a delayed effect of DMF. Meanwhile, other anti-inflammatory cytokines, IL-4 and IL-13, increased with relatively large effect sizes. The subsequent experiment shows that DMF pretreatment also alleviated anxiety- and cognitive dysfunction-like behaviors, measured at 6-7 weeks post-surgery. Additionally, this treatment significantly diminished SNI-induced protein ATF-3 - a neuronal injury marker - in L4-6 DRG at day 49 post-surgery. Nuclear factor E2-related factor 2 (Nrf2), a major regulator of the antioxidant and anti-inflammatory response, appears to be linked with DMF protective mechanisms, with trigonelline, an Nrf2 inhibitor, largely abolishing its effects. In conclusion, preexposure to an anti-inflammatory drug improved rats’ resilience to long-term allodynia and pain-related manifestations. This suggests the immune system’s involvement in the susceptibility to chronic pain and its comorbidities. Regarding mechanisms, Nrf2 and its inflammatory downstream effectors, as well as ATF-3, play a significant role, although potential contributions of other factors cannot be dismissed.
Online verfügbar: 9. Mai 2025, Artikelversion: 20. Mai 2025
Gesehen am 19.08.2025